UPAYA PEMERINTAH DALAM MENERAPKAN PRINSIP EKONOMI BIRU UNTUK MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN SUMBER DAYA KELAUTAN - zimtya zora (JURNAL HUKUM DAS SOLLEN, 2025)
ABSTRACT As global attention toward sustainable economic development continues to increase, the blue economy concept has gained relevance as an alternative framework. This approach merges sustainable development objectives with the responsible management and utilization of marine-based resources. Both national and local governments hold a strategic position in enforcing blue economy principles to ensure the sustainable governance of maritime resources. This study adopts a normative juridical method, which involves identifying governing legal norms, principles, and doctrines to formulate responses to the legal questions examined. Supporting materials include previous scholarly findings and verified data obtained from official governmental platforms. Based on the analysis provided, the Government has introduced five primary policy directions as part of Indonesia’s blue economy implementation framework : quota-based regulated fishing, expansion of marine conservation territories, development of marine and freshwater aquaculture, advancement of marine waste management, and sustainable administration of small islands and coastal regions. Furthermore, strategies to overcome challenges in applying blue economy principles include conducting detailed and systematic resource mapping—particularly in the fisheries sector—enhancing monitoring mechanisms, and fostering cooperation with relevant agencies, private sector actors, and the wider community. This research concludes that the Government has undertaken significant initiatives and responsibilities in integrating blue economy principles to promote sustainable marine resource development in support of the national vision of Golden Indonesia 2045 within the maritime domain. Keywords : Government, Blue Economy, Sustainable Development, Marine Resources.